The Fixer as a Subject of Media Management in International Journalistic Projects: Ukrainian Experience, 2022–2025 - Nasad, N. V.; Biriukov, V. M. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article is devoted to the analysis of fixing as a specific form of managing international journalistic projects under wartime communication conditions. The study applies case study, content analysis, and participant observation methods to identify managerial, communicative, and ethical aspects of fixers’ activities during the full-scale war in Ukraine. It has been found that the fixer performs complex functions – from logistical support to strategic risk and communication management. Within international media projects, the fixer acts as a field manager, coordinator of intercultural interaction, and agent of cultural mediation, ensuring the reliability and safety of information flows. The managerial functions of the fixer – planning, organization, communication, control, and crisis management – have been identified and shown to correspond to the principles of modern media management. The fixer is defined as a project manager, risk coordinator, and cultural mediator who ensures effective inter-organizational interaction between international media structures and local communities. The paper proposes a conceptual model of the fixer as an agent of media management, integrating managerial, analytical, and ethical competencies. Based on the Ukrainian experience, the study outlines directions for the professionalization of fixer activity: establishing a Fixers’ Association, developing an ethical code, introducing educational programs in crisis media management, and creating a system of state support.